Filesystem Consistency Check For Universal Disk Format - Vladyka, Vojtěch (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2017)
This paper focus on creation of tool for detection and correction UDF filesystem in OS Linux. It describes all available error detection mechanisms described by ECMA-167 standard and possible solution how to correct found errors.
Keywords: UDF; fsck; Linux; error detection; error correction; filesystem